Population structure and diversity of the needle pathogen Dothistroma pini suggests human-mediated movement in Europe - van der Nest, Ariska; Wingfield, Michael J.; Sadiković, Dušan; Mullett, Martin S.; Marçais, Benoit; Queloz, Valentin; Adamčíková, Katarina; Davydenko, Kateryna; Barnes, Irene (Frontiers in Genetics, 2023)
Dothistroma needle blight is an important disease of Pinus species that can be caused by one of two distinct but closely related pathogens; Dothistroma septosporum and D. pini. Dothistroma septosporum has a wide geographic distribution and is relatively well-known. In contrast, D. pini is known only from the USA and Europe, and there is a distinct lack of knowledge regarding its population structure and genetic diversity. The recent development of 16 microsatellite markers for D. pini provided an opportunity to investigate the diversity, structure and mode of reproduction for populations collected over a period of 12 years, on eight different hosts in Europe. In total, 345 isolates from Belgium, the Czech Republic, France, Hungary, Romania, Western Russia, Serbia, Slovakia, Slovenia, Spain, Switzerland and Ukraine were screened using microsatellites and species-specific mating type markers. A total of 109 unique multilocus haplotypes were identified and structure analyses suggested that the populations are influenced by location rather than host species. Populations from France and Spain displayed the highest levels of genetic diversity followed by the population in Ukraine. Both mating types were detected in most countries, with the exception of Hungary, Russia and Slovenia. Evidence for sexual recombination was supported only in the population from Spain. The observed population structure and several shared haplotypes between non-bordering countries provides good evidence that the movement of D. pini in Europe has been strongly influenced by human activity in Europe.